Innovation System Reform in Indonesia and Vietnam: A new Role for Universities? - Erik Baark (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
This paper introduces the importance of the role of universities in emerging economies such as Indonesia and Vietnam, underscoring the need for universities to contribute more extensively to the dynamic development of innovation systems. The theoretical approach is a functional analysis of innovation systems, identifying essential issues that call for recognition among policymakers and in society generally. Innovation systems in Indonesia and Vietnam share some weaknesses, particularly in comparison with innovation systems in more advanced countries. There is limited ability to mobilize the resources required for innovation, as the investment in research and development as percentage of GDP is relatively low and dominated by public funding with little contribution from private sources. Financial regulation for universities seriously hampers the development of university–industry linkages. It is essential that universities gain more autonomy in order to move beyond their current role in training of skilled human resources to providers of innovation.